New species and records of Lathrobium from the Palaearctic region, primarily from Nepal (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2014)
Eighteen species of Lathrobium Gravenhorst, 1802 from Nepal (16 species) and China (2 species) are described and illustrated: L. semicirculatum sp. n. (E-Nepal; L. nepalense group); L. constrictum sp. n. (E-Nepal; L. discissum group); L. descendens sp. n. (W-Nepal; L. deuvei group); L. ascendens sp. n. (W-Nepal; L. deuvei group); L. rude sp. n. (C-Nepal: Dhaulagiri; L. emodense group); L. latibasale sp. n. (W-Nepal; L. pectinatum group); L. eques sp. n. (W-Nepal; L. pectinatum group); L. equitans sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. abruptum sp. n. (W-Nepal; L. pectinatum group); L. kemum sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. flexaculeatum sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. rectaculeatum sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. curvaculeatum sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. hebes sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. imberbe sp. n. (W-Nepal; L. pectinatum group); L. plicatum sp. n. (C-Nepal: Dhaulagiri; L. pectinatum group); L. glabrimpressum sp. n. (China: Yunnan: Gaoligong Shan; group assignment uncertain); L. smetanai sp. n. (China: Gansu: Dalija Shan; L. lentum group). Based on new material, a redescription and new illustrations of L. aculeatum Coiffait, 1982 are provided. Recently collected material of L. calcaratum Assing, 2012 suggests that the holotype of this species may have been mislabelled and that, consequently, the type locality is erroneous. The species previously assigned to the L. aculeatum group are moved to the L. pectinatum group, and the L. aculeatum group is discarded. Several species of the L. pectinatum group were found to be subject to a sexual dimorphism of body size. Additional records of six named species are reported from the West Caucasus (2 species) and from Nepal (4 species). Including the newly described species, the genus is currently represented in the Himalaya by 68 species in ten species groups, in China by 189 species, and in the Palaearctic region by 536 named species and ten subspecies. Keywords Coleoptera, Staphylinidae, Paederinae, Lathrobiina, Lathrobium, Palaearctic region, Nepal, China, Caucasus, taxonomy, new species, species groups, sexual size dimorphism, diversity, new records. Nomenclatural Acts abruptum Assing, 2014 (Lathrobium), spec. n. ascendens Assing, 2014 (Lathrobium), spec. n. constrictum Assing, 2014 (Lathrobium), spec. n. curvaculeatum Assing, 2014 (Lathrobium), spec. n. descendens Assing, 2014 (Lathrobium), spec. n. eques Assing, 2014 (Lathrobium), spec. n. equitans Assing, 2014 (Lathrobium), spec. n. flexaculeatum Assing, 2014 (Lathrobium), spec. n. glabimpressum Assing, 2014 (Lathrobium), spec. n. hebes Assing, 2014 (Lathrobium), spec. n. imberbe Assing, 2014 (Lathrobium), spec. n. kemum Assing, 2014 (Lathrobium), spec. n. latibasale Assing, 2014 (Lathrobium), spec. n. plicatum Assing, 2014 (Lathrobium), spec. n. rectaculeatum Assing, 2014 (Lathrobium), spec. n. rude Assing, 2014 (Lathrobium), spec. n. semicirculatum Assing, 2014 (Lathrobium), spec. n. smetanai Assing, 2014 (Lathrobium), spec. n.